Pemanfaatan Biogas Sebagai Sumber Energi Terbarukan di Dusun Jambu - Andari, Muhammad Zidan Alghazi; Hastuti, Febri Dwi; Risha, Hanifah Tri Noor; Ridoni, Igniza; Arissa, Putri; Yunas, Mawla Afadha; Adrian, Arkana Kenza Pria; Nadheani, Hadhainada; Giantara, Muhammad Angger Dipa; Imanullah, Rizal Aulia Yahya; Asroni, Asroni (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
The socialization and implementation of biogas technology in Dukuh Jambu was carried out as a solution to the issue of poorly managed organic waste from livestock farming and the high dependence of the community on fossil fuels. The main goal of this program is to increase awareness and skills among the community in processing livestock waste into environmentally friendly and economical renewable energy. The methods used in this program include socialization, technical training, and the installation of a non-fixed dome biodigester-based biogas system, which is more flexible, easier to install, and more affordable compared to the fixed dome system. This activity involves active community participation, both in the installation process and in outreach activities related to the utilization and maintenance of the biogas system. The results of the program show that the implemented biogas system is capable of producing sufficient methane gas for household needs, with an average daily production of 1 cubic meter per biodigester unit. Additionally, the fermentation residue can be utilized as organic fertilizer, which enhances soil fertility and increases local agricultural productivity. Another positive impact is the reduction of environmental pollution caused by the accumulation of livestock waste and fuel cost savings for the community, where households using biogas experienced a reduction in LPG consumption by up to 50%. Although this program faced challenges such as the initial lack of knowledge among the community and technical issues in system maintenance, intensive outreach and mentoring efforts successfully improved the community's understanding and skills in managing the biogas system independently. This program has the potential to be further developed by expanding the application of biogas to more households and small businesses. The proposed follow-up actions include enhancing community capacity through advanced training, integrating biogas with sustainable agriculture, and strengthening government policy support to enable wider adoption of this technology. Therefore, this program not only contributes to better waste management but also serves as a strategic step in promoting the transition to clean and sustainable energy